Mapping Network Relationships from Spatial Database Schemas to GML Documents - Hora, Andre C.; Davis Jr, Clodoveu A.; Moro, Mirella M. (Journal of Information and Data Management, 2011)
Spatial data encoded in GML documents are used in various applications and are especially suited to storing, manipulating and exchanging geographic information. However, a large share of currently available spatial data is stored in spatial databases. This article presents a method to map arcs and nodes, organized in a network using spatial relationships, from a spatial database to a GML document. Specifically, a geographical conceptual schema and the corresponding GML schema are used as guide to retrieve and reorganize networking information found in the spatial database, thus generating a GML document. The proposed methodology is verified in a case study, in which networking relationships from real-world databases are mapped to GML documents that can be queried using standard XML languages such as XPath and XQuery.